Territorial dimension of development as a new paradigm of the European cohesion policy for the years 2014-2020 - Wyrwa, Joanna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The aim of this article is to identify the fundamental changes in the approach to programming and financing the development in the years 2014-2020, to present mechanisms and instruments of urban policy supported by EU funds, as well as practical aspects concerning territorial delimitation of urban functional areas. Considerations shall be based on studies of program source documents relating to functional areas
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 476, s. 39-48
Keywords: regional development; integrated development; functional area; rozwój regionalny; rozwój zintegrowany; obszar funkcjonalny